The Effect of Wudhu on Reducing Anxiety Level - Murodi Murodi; Syahrullah Syahrullah; Nahuda Nahuda; Munaya Fauziah; Irna Hasanah (Indonesian Journal of Islam and Public Health, 2022)
Islam teaches its people to maintain health and cleanliness in any case. One way is to perform Wudhu. Wudhu is a direct command from Allah SWT which is written in the Qur'an as a way of purification before praying. However, if we examine further the procedures for performing Wudhu in accordance with what was taught by the Prophet Muhammad, it turns out that it contains hidden benefits. This study used a literature review method by examining from the health side based on the results of previous studies. Discussing the benefits of Wudhu for health, factored in a person's physical condition. By doing Wudhutherapy, it turns out that it can reduce anxiety levels so that a sense of comfort and calm arises. Of course, this Wudhu therapy must be done properly so that the nerve points on the body are touched when Wudhuis performed. Wudhu also has other benefits that not many people know. Apart from doing Wudhu, it also has other benefits, namely it can create a sense of calm, reduce anxiety levels, changes in blood pressure and so on.